MANAJEMEN PEMERINTAHAN OLEH DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN PELALAWAN DALAM PROGRAM BANTUAN RUMAH SEHAT LAYAK HUNI DI KECAMATAN UKUI TAHUN 2018 - Nur Fitri; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Fulfilling the need for a place to live is the right of every citizen, because it is guaranteed by the 1945 Constitution in Article 28H Paragraph 1 which states that "everyone has the right to live in physical and spiritual prosperity, to live, and to have a good and healthy living environment and the right to health services. The government hereby provides a program of healthy, livable houses for the poor who do not have or already own a house but are not yet livable in Ukui Sub-district, Pelalawan Regency. The problem with this research is that this program is not right on target because the program recipients are still well-off people, besides that in terms of development, it exceeds the predetermined time limit, which is 90 working days or for three months. The purpose of this study is to find out government management by the Public Works and Spatial Planning Department of Pelalawan Regency in the Healthy Homes for Living Assistance program in Ukui District and the inhibiting factors for Government management in the Healthy Homes for Liveable Assistance programs in Ukui District. In this study using the theory of Government Management Zaidan Nawawi. Where according to Zaidan Nawawi there are five aspects of management, namely, Planning, Organizing, Coordinating, Actuating, Controling. This study uses research methods with qualitative research approaches and types. This research was conducted at the Department of Public Works and Spatial Planning, Pelalawan Regency. Data collection techniques by means of interviews and documentation. Based on the results of the study, it can be concluded that the Department of Public Works and Spatial Planning has not been maximized in the implementation of the Decent Healthy Home assistance program. This program is still not right on target, those who should get it don't get it and those who shouldn't get it actually get it.The PUPR office must be more selective in verifying program recipient data so that this program is in line with its original goal of helping the poor to get a better life. Keywords: Government Management, Programs, Livable Houses